Research Methods in Pedagogy (Journal of Science-Innovative Research in Uzbekistan, 2025)
Research in pedagogy encompasses a variety of methods that aim to explore, evaluate, and improve teaching and learning practices. This article explores the key research methods commonly used in the field of pedagogy, including qualitative, quantitative, and mixed methods approaches. The article discusses the strengths and limitations of each method, as well as their applications in educational settings. Additionally, it highlights the importance of aligning research methods with educational goals and the context of the teaching environment. By understanding and employing appropriate research methods, educators and researchers can contribute to the development of more effective pedagogical strategies, ultimately enhancing student learning outcomes.